Degradation of Rhodamine B by Visible Light Driven MoO3TiO2 Core-Shell Photocatalyst - Liu, Hejin (Langmuir : the ACS journal of surfaces and colloids, 2024)
In this study, a MoO3TiO2 composite core-shell material was developed to remove Rhodamine B (RhB) dye through synergistic adsorption and photocatalytic degradation. n-n heterostructures were formed by coupling n-type semiconductors to enhance the efficiency of photocarrier separation and photocatalytic performance. MoO3, which possesses strong adsorption capacity, was primarily used as a dye adsorbent. Additionally, the formation of an n-n heterojunction with TiO2 enabled MoO3 to expand the photocorresponding range of TiO2, leading to the generation of superoxide (O2•) and hydroxyl (•OH) free radicals for dye degradation. The experimental results demonstrate that the MoO3@TiO2 core-shell composite exhibits excellent performance for RhB dye removal, with adsorption and degradation rates reaching 35.7 and 70.3%, respectively, even at low catalyst concentrations. This approach offers new insights into the development of MoO3 core-shell photocatalysts